THE SOCIOPRAGMATIC DIMENSIONS OF APOLOGISING AS A COMMUNICATIVE ACT - Harutyunyan, Gohar; Azaryan, Shushanik (Armenian Folia Anglistika, 2025)
In the context of sociopragmatics, communication plays a fundamental role in the expression and negotiation of social norms and expectations. Effective communication hinges on an understanding of sociopragmatic principles, such as politeness strategies and speech acts. This study aims to examine the communicative act of apologizing, focusing on the speaker- sign-listener- social context correlation. The objective is to determine how the choice of various linguistic forms influences perceptions of politeness and social appropriateness in communication. By analyzing different types of apologies, the present paper seeks to identify apology strategies within the communication process and to evaluate how these strategies facilitate the repair of relationships and the restoration of trust. Ultimately, the research enhances our understanding of the power of language in interpersonal communication and underscores the significance of effective apologies in contemporary society. The findings provide insights into the diverse linguistic and social factors that contribute to effective apologies, which typically involve acknowledging responsibility for wrongdoing, expressing remorse, and offering reassurances for future conduct.